Employed inventors, inter-firm mobility, bonus pay with multi-stage R&D processes, and optimal innovation policy - Diego d'Andria (European Commission, Joint Research Centre (JRC), 2016)
A temporary change in pay to employed inventors around the time of patent application has been observed in a number of countries. A theoretical model is here developed to provide an explanation to said findings based on the idea that inventors may be able to use the knowledge previously generated while working in a firm, in a rival company. The model features firms who hire workers in R&D functions to make product innovations. The innovation process consists of distinct phases separated by a patent application. Firms compete to attract workers, and workers can transfer part of the generated new knowledge to a new employer. Results suggest that the capital intensity of R&D investments, and the type and size of knowledge spillovers, may affect the probability to observe bonus pay at the time of a patent application. Different tax incentives and subsidies are then studied as a means to correct for possible under-investment of capital. We study the effect of a patent box, a subsidy to R&D capital investments, and a subsidy to bonus pay. When market rivalry prevails over positive knowledge externalities, a bonus pay incentive was found to obtain the social first-best while a patent box or a subsidy to capital investment would cause overinvestment. When positive knowledge externalities prevail, either a patent box or a subsidy to capital investment obtain the social optimal level of capital investments.
Keywords: O3; J31; H23; H25; 330; innovation; bonus pay; moving researchers; patents; R&D tax incentives